Rebranding and brand positioning in customers of a gastronomic company - Vargas Alaya, Patrick Slater; Noel Zavaleta, Wilmer Daniel; Mendoza Castillo, Alvaro Larry Luis Felipe; Ventura Aguilar, Henry Elder; Valderrama Puscan, Marlon Walter (LACCEI, 2024)
The purpose of this research was to determine the relationship between rebranding and brand positioning in customers of the company Casa Quimuk, Trujillo 2023. For this purpose, applied research of non-experimental design with a quantitative approach and correlational scope was used. The population consisted of 1010 customers of Casa Quimuk, of whom a sample of 279 customers was taken, and a questionnaire designed with 26 questions and indicators with a Likert scale was used as an instrument for data collection. The results showed the existence of an average positive correlation Rho=0.604 and significant p-value 0.000 between the variables rebranding and brand positioning, the existence of average levels of rebranding and brand positioning was also obtained, as well as average and low positive correlations between rebranding and brand positioning dimensions. The conclusions were that, the adequate brand management becomes an instrument that helps to solve the brand positioning problems that occur, likewise, points such as the experiences that customers take to mind, generating brand difference, applying marketing strategies focused on strengthening the brand image, creating an emotional bond and trust through experiences, evaluations on the perception of brand quality in customers, became tools that help to solve the problems of brand recognition, familiarity and satisfaction.